Organizational justice and job crafting as predictors of work engagement: The moderating role of perceived organizational support among police officers - Eka Putri Purwitasari; Retno Dwiyanti; Mohd Nazri Abdul Rahman; Mahdi Anbari; Endah Silawati (Universitas Ahmad Dahlan, 2026)
Work engagement among police officers plays a strategic role in maintaining social stability, security, and public order within dynamic political and economic environments. The demands of police work, including long working hours, high levels of risk, and unpredictable assignments, require officers to proactively adjust their work according to their preferences, skills, and capacities in order to perform effectively. This study aims to examine the effect of job crafting and organizational justice on work engagement, as well as to test the moderating role of perceived organizational support. This study employed a quantitative approach involving 200 police officers at the Banyumas Police Resort. The sampling technique used was proportional random sampling. Data analysis was conducted using Smart-PLS version 4. The results indicate that job crafting has a significant positive effect on work engagement. In addition, perceived organizational support significantly moderates the relationship between job crafting and work engagement, strengthening its positive effect. In contrast, organizational justice does not have a significant effect on work engagement, and perceived organizational support does not moderate the relationship between organizational justice and work engagement. These findings suggest that, within a hierarchical police organization, work engagement is more strongly influenced by individual initiative in managing work than by perceptions of organizational justice. The study highlights the importance of organizational support and opportunities for officers to engage in job crafting to enhance work engagement. Police organizations are encouraged to develop a more supportive and adaptive work environment to address dynamic job demands.